Enhancing Letter Recognition in Students with Mild Hearing Impairment through Flashcard-Based Phonics: A Single Subject Intervention Study - Hilmi Maulid Datul Hasanah; Budi Susetyo; Neni Meiyani (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine the effectiveness of a flashcard-based phonics method in improving letter recognition among students with mild hearing impairment. A Single Subject Research (SSR) design with an A-B-A pattern was applied to one second-grade student at SLBN A Citeureup, Cimahi City. Data were collected through repeated written tests and practical tasks during baseline-1, intervention, and baseline-2 phases, then analyzed using within and between-condition visual analysis. The findings showed that the student’s letter recognition score increased from 50% in baseline-1 to 68.9% during the intervention, and further rose to 84.5% in baseline-2. An overlap percentage of 0% indicated a strong intervention effect. These results suggest that flashcard-based phonics is effective for enhancing early literacy skills in learners with mild hearing impairment. Practically, the combination of flashcards and phonics supports visual learning characteristics and helps strengthen the relationship between letter symbols and sounds in more structured literacy instruction. It also offers a simple alternative for special education classrooms.